Safety Profile and Neurocognitive Function Following Acute 4-Fluoroamphetamine (4-FA) Administration in Humans - de Sousa Fernandes Perna, Elizabeth B.; Theunissen, Eef L.; Dolder, Patrick C.; Mason, Natasha L.; Hutten, Nadia R. P. W.; Toennes, Stefan W.; Kuypers, Kim P. C.; Ramaekers, Johannes G. (Frontiers in Pharmacology, 2018)
Availability of novel psychoactive substances (NPS) exponentially increased over the last years. Risk evaluations of NPS are hampered by the lack of pharmacological studies in humans on health parameters. The aim of the present study was to evaluate safety and neurocognitive function of healthy volunteers (N = 12) who received single doses of 100 and 150 mg 4-fluoroamphetamine (4-FA), a phenethylamine that has been associated with severe cardiovascular and cerebrovascular complications. The study was set-up as a placebo controlled, within subject, phase 1 trial as it was the first to administer 4-FA to humans under controlled conditions. Overall, 4-FA produced a strong elevation in blood pressure up until 4–5 h after administration that was followed by a sustained increase in heart rate. After an interim review of safety data from five participants, a decision was taken to cancel administration of 150 mg. We subsequently obtained complete datasets for placebo and 100 mg 4-FA treatments only. Effects of 4-FA on mood and neurocognitive function were most distinct at 1 h post drug and included significant elevations of vigor, friendliness, elation, arousal, positive mood, as well as improvements in attention and motor performance. Negative affect was also reported as time progressed in the acute phase and even more so during the subacute phase. Overall, the influence of 4-FA on vital signs, mood, and neurocognition was similar to that observed with other stimulants. Present findings confirm clinical observations of acute toxicity among 4-FA users and warrant warnings about potential health risks associated with 4-FA use.